3t-2t-1=15

Simple and best practice solution for 3t-2t-1=15 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3t-2t-1=15 equation:


Simplifying
3t + -2t + -1 = 15

Reorder the terms:
-1 + 3t + -2t = 15

Combine like terms: 3t + -2t = 1t
-1 + 1t = 15

Solving
-1 + 1t = 15

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '1' to each side of the equation.
-1 + 1 + 1t = 15 + 1

Combine like terms: -1 + 1 = 0
0 + 1t = 15 + 1
1t = 15 + 1

Combine like terms: 15 + 1 = 16
1t = 16

Divide each side by '1'.
t = 16

Simplifying
t = 16

See similar equations:

| 2x+7x-8=19 | | 15p-12p-p+3=17 | | 15-12p-p+3=17 | | I-17.4=33 | | 11h-11h+h=20 | | 2(t+5)=7 | | 2r-r+4r-3r=20 | | 16=-16t^2+24t+0 | | D-1890=8242 | | -8x(x+1)-8=6-9x | | 15y-11y+6y=10 | | 6g-4g+g-3g+g=17 | | 11/3×12/1= | | 15h-11h=12 | | x+12=9x-5 | | 14m-13m=5 | | 7a+a=16 | | x(1/3)(3) | | 4(7x+y)= | | 5y-2y=3 | | 6/2=15/m | | 6/2r15/m | | 12v-10v=18 | | 6h^2+11h+4=0 | | 2x+6=2-3x | | -13x-(19)=-6 | | X^2+5x+6=42 | | 4y=7+8x | | 25=s+13-45s | | 12=-8t^2+24t+5 | | Y+30= | | -4=(6-2x) |

Equations solver categories